Longitudinal Association Between Intimate Partner Violence and Alcohol Use in a Population Cohort of South African Women - Yalch, Matthew M. (Journal of interpersonal violence, 2023)
Intimate partner violence (IPV) is a common traumatic stressor for women worldwide, especially for women living in low-and-middle-income countries. One of the most common correlates of IPV victimization is alcohol use, but the dynamics of IPV and drinking among women are not well understood. Although some research suggests that women drink in the aftermath of IPV to cope with distress related to the violence they experienced, other studies imply that higher levels of alcohol use among one or both partners in a relationship make violence more likely. In this study, we examine this question in a secondary analysis of a longitudinal study of a population cohort of pregnant women in South Africa (N = 1238) using a Bayesian approach to latent growth curve structural equation modeling. Results indicate that on average, IPV decreases and alcohol use increases over time and that these trajectories are associated with each other. Further, results suggest that although IPV drives drinking (rather than the other way around), higher average levels of alcohol use are associated with a slower decrease in IPV. Findings have implications for future research on the association between IPV and alcohol use, as well as for clinical intervention for women who experienced IPV.